2009
DOI: 10.1007/s11205-008-9428-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Material Hardship among the US Population of Women with Disabilities Using Latent Class Analysis

Abstract: Material hardship, Disability, Latent class analysis, Poverty,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Latent class analysis provides additional information by identifying underlying subgroups that are mutually exclusive and differ qualitatively on the types and patterns of needs experienced. 7,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Latent class analysis provides additional information by identifying underlying subgroups that are mutually exclusive and differ qualitatively on the types and patterns of needs experienced. 7,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Research by Boushey and Gundersen (2001) made a distinction between material hardships that are critical in terms of meeting basic needs (e.g., food insufficiency) versus those that are serious (e.g., lack of adequate childcare). Other researchers identified underlying dimensions of the concept of material hardship using latent class analysis (Rose, et al, 2009) and factor analysis (Carle et al, 2009). However, no standard measure of material hardship exists in the literature (Ouellete, Burstein, Long, & Beecroft, 2004).…”
Section: Materials Hardship and Povertymentioning
confidence: 99%
“…Research exploring the relationship between material hardship and work-limiting disabilities (Rose et al, 2009;She & Livermore, 2007) and health problems (Heflin, 2006;Heflin & Butler, 2013) indicated that this is the case. Other studies have demonstrated that transportation problems were associated with being disconnected from work and public assistance (Powers, Livermore, & Davis, 2013), and low levels of education served as a barrier to employment (Dworsky & Courtney, 2007).…”
Section: Income-and Resource-packaging Model Of Materials Hardshipmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies investigate additional facets of material hardship, including food insecurity (Rose, Parish, and Yoo 2009; Huang, Go, and Kim 2010), difficulties in meeting basic needs (She and Livermore 2007, Rose, Parish, and Yoo 2009), and multidimensional poverty measures that include measures of deprivation in social integration and civic engagement (Brucker et al 2014). These studies reach a consensus that, regardless of the measure of material hardship or multidimensional poverty used, people with disabilities experience higher rates of material hardship than people without disabilities, even adjusting for other variables that might predispose people with disabilities to a higher risk of material hardship (e.g., lower levels of education, higher rates of unemployment).…”
Section: Introductionmentioning
confidence: 99%